The Digital Euro: Functionality and Critical Appraisal - Friedrich Thießen (Wirtschaftsdienst)
Abstract In October 2020, the ECB published the foundational paper on the digital euro. In spring 2021, it surveyed individuals and companies on these proposals, the results of which were published in April 2021. This paper compares the design proposals with the survey results as well as the activities of competitive systems. It shows that important aspects remain unresolved. The survey showed that global payment capability is an urgent desire. Easy-to-use ‘onboarding’ without IBAN is also expected. Another goal should be the independence of European payments from third-party intervention, as was the case in the Iran-U.S. conflict. A reform of the correspondent banking network via SWIFT with a centralisation of balance settlement could possibly deliver results as good as those of the ECB’s digital money.